Geomagnetic activity and the North Atlantic Oscillation - Bucha, Václav, 1928- (Studia Geophysica et Geodaetica)
1_The North Atlantic Oscillation (NAO) is the prominent pattern of winter climate variability that has a strong effect on weather in the North Atlantic region and the adjacent continents. At present, uncertainty prevails as to the mechanisms controlling the variability of the NAO. It is also difficult to explain why the positive phase of the NAO has prevailed over the past 37 years (1972–2008). We found high positive correlation coefficients between geomagnetic activity (used as a measure of solar wind intensity) and the NAO indices that equal 0.76 for 1962–1994 and 0.63 for 1961–2011. Positive correlations of the distribution of surface air temperature with the NAO and similarly with geomagnetic activity occur in the Northern Hemisphere. These results encourage our search for possible causes controlling the NAO. We have found that at times of high geomagnetic activity the NAO index is positive and magnetic reconnection may enable the solar wind to initiate downward winds in the magnetosphere. 2_Wind anomalies originate at the edge of the stratospheric polar vortex and propagate downward through the troposphere taking part in the intensification of the vortex and of the westerlies. Stronger northerly winds over Greenland carry cold air southward and, together with the enhanced westerlies, advect the warm air from the Atlantic along the deep Icelandic low into Eurasia increasing temperatures there. On the other hand, at times of low geomagnetic activity, the NAO index is negative and the stratospheric polar vortex is weak. Warm air from the subtropics is carried into the Arctic and a rapid amplification of planetary waves propagating upward may cause displacement or even splitting of the weak vortex and sudden stratospheric warming. During this negative NAO phase the weakened westerlies allow more cold air to build up over North America and Eurasia. Václav Bucha. Obsahuje seznam literatury